Ball-milled magnetic biochar for efficient activation of hydrogen peroxide to remove norfloxacin: Performance and mechanism - Tushan Zhong; Yue Fu; Yingyi Chen; Yunqiang Yi; Weirui Chen; Zenghui Diao (Journal of Environmental Chemical Engineering, 2026)

Characterization of Viable and Non-viable Microbes in PM2.5 at a Mountain Site in Southern China - Yu Zheng; Senchao Lai; Zhaokang Ruan; Yuhong Feng; Yuhan Shen; Yaoyao Fu; Xinhui Bi; Dingli Yue; Zhifeng Shi; Yingyi Zhang (Aerosol Science and Engineering, 2026)

Priming Effects on Soil Organic Matter Mineralization by Carbon Substrates: A Global Meta‐Analysis - Hongxin Dong; Yingyi Fu; Shanshan Dai; Peng He; Yu Luo; Margaret A. Oliver; William R. Horwath; Lu‐Jun Li (Global Change Biology, 2026)
Priming effects (PE) on soil organic matter (SOM) mineralization depend strongly on the type of carbon substrates added. It is crucial to understand the PE induced by various carbon substrates for predicting SOM dynamics and soil‐atmosphere carbon feedback. We conducted a meta‐analysis of 8015 observations from 283 articles to evaluate how carbon substrates (plant residues, root exudates, biochar, and degradable microplastics) regulate the mineralization of SOM through PE. Results demonstrated that all these types of carbon substrates increased SOM mineralization, which induced a positive PE. Plant residues induced the highest average PE, followed by root exudates, biochar, and degradable microplastics. Compared to soils without carbon substrate inputs, the rate of SOM mineralization increased by 113% in soil with cellulose‐rich non‐woody residues, whereas it increased by only 25% in soil with lignin‐rich woody residues. The mineralization of SOM increased by organic acids (151%) was greatest in root exudates, followed by monosaccharides (60%) and polysaccharides (12%). The strong mineralization induced by organic acids was probably related to the release of more mineral nutrients by reducing soil pH. The PE on SOM mineralization by woody biochar with high aromatic carbon content (48%) was greater than that of non‐woody biochar with high alkyl carbon content (43%). Microplastics with rapidly degradable polyhydroxyalkanoates induced more SOM mineralization (258%) than polybutylene succinate (61%) and polybutylene adipate‐co‐terephthalate (21%). The SOM priming was positively correlated with soil clay and incubation moisture, and negatively correlated with soil organic carbon, total nitrogen, soil C:N ratio, dissolved organic carbon, microbial biomass carbon, carbon input rate, incubation temperature, and soil depth. These results show that the positive PE is ubiquitous in soil ecosystems; its magnitude is linked intrinsically to the physicochemical characteristics and source of exogenous carbon substrate.

Diversity loss of soil microbiome stimulates soil carbon emissions - Haibo Pan; Yingyi Fu; Hairong Tu; Yongxing Cui; Beibei Chen; Jiejun Qi; Ziheng Peng; Shi Chen; Chunling Liang; Jiai Liu; Xiaomeng Li; Min Gao; et al. (Soil Biology and Biochemistry, 2026)

Microbial metabolisms determine soil priming effect induced by organic inputs - Yingyi Fu; Wanling Liu; Zhiyi Chen; Marc Redmile-Gordon; Chao Liang; Caixian Tang; Georg Guggenberger; Shaobin Yan; Liming Yin; Jingjing Peng; Lukas Van Zwieten; Peng Wang; et al. (Soil Biology and Biochemistry, 2025)

Deciphering the microbial players driving straw decomposition and accumulation in soil components of particulate and mineral-associated organic matter - Yingyi Fu; Yuqi Xu; Qiang Wang; Lukas Van Zwieten; Chao Liang; Jianming Xu; Georg Guggenberger; Yu Luo (Soil Biology and Biochemistry, 2025)

Faster soil organic carbon turnover in MAOM versus POM: straw input causes larger microbial driven soil organic carbon decomposition but higher straw accumulation in MAOM - Xiongsheng Yu; Lili Wang; Qiang Wang; Guoyan Zhou; Han Sun; Georg Guggenberger; Yongfu Li; Kuzyakov Yakov; Yu Luo; Yingyi Fu (Soil and Tillage Research, 2025)

Deciphering the microbial mechanisms underlying glucose induced soil priming effects under low and high nutrient levels - Jiaqi Wang; Xichang Zhang; Yingyi Fu; Lukas Van Zwieten; Han Sun; Georg Guggenberger; Lingfei Hu; Yu Luo; Tida Ge; Yakov Kuzyakov (European Journal of Soil Biology, 2025)

Mass deposition of microbes from wildfire smoke to the sea surface microlayer - Siyao Yue; Yafang Cheng; Lishan Zheng; Senchao Lai; Shan Wang; Tianli Song; Linjie Li; Ping Li; Jialei Zhu; Meng Li; Lianfang Wei; Chaoqun Ma; et al. (Limnology and Oceanography, 2025)
Microbes in the sea surface microlayer (SML) are key to connecting the ocean and the atmosphere, affecting the exchange of matter, momentum, and heat at the interface. However, their sources have never been quantified systematically. Seawater has long been deemed their major source, whereas atmospheric deposition is regarded as trivial or merely providing additional nutrients. Here, combining atmospheric observations and quantitative budget analyses, we show that during the Indonesian peatland wildfire events the smoke can directly deposit abundant microbes into the SML, which can be comparable to the estimated supply from seawater and potentially diversify the microbial community of the SML. This land–air–ocean interaction is relevant for global climate, as it may induce previously unknown effects on the air–sea interactions, especially in an increasingly warming future with more intensifying wildfires.

Study on the role of mitophagy and pyroptosis induced by nano-silver in testicular injury - Deyu Zhu; Yingyi Li; Min Liu; Yufen Yang; Jiayu Fu; Liyu Su; Feng Wang; Yuyan Cen; Yanna Zhou; Yan Li (Food and Chemical Toxicology, 2025)

Shift of microbial taxa and metabolisms relying on carbon sources of rhizodeposits and straw of Zea mays L - Yingyi Fu; Yu Luo; Jiejun Qi; Xinhua He; Haoqing Zhang; Georg Guggenberger; Jianming Xu (Soil Biology and Biochemistry, 2024)

Global insights into endophytic bacterial communities of terrestrial plants: Exploring the potential applications of endophytic microbiota in sustainable agriculture - Lukuan Huang; Yingyi Fu; Yaru Liu; Yijie Chen; Tingzhang Wang; Meixia Wang; Xianyong Lin; Ying Feng (Science of The Total Environment, 2024)

Analysis of amino acid enantiomers in ambient aerosols: Effects and removal of coexistent aerosol matrix - Ying Li; Xiaoying Li; Libin Wu; Luhan Shi; Shan Wang; Pingqing Fu; Yingyi Zhang; Senchao Lai (Journal of Environmental Sciences, 2024)

Effects of intercropping on safe agricultural production and phytoremediation of heavy metal-contaminated soils - Yaru Liu; Lukuan Huang; Zheyu Wen; Yingyi Fu; Qizhen Liu; Shunan Xu; Zhesi Li; Chanjuan Liu; Chao Yu; Ying Feng (Science of The Total Environment, 2023)

Carbon capture and storage technology by steel-making slags: Recent progress and future challenges - Yingyi Zhang; Laihao Yu; Kunkun Cui; Hong Wang; Tao Fu (Chemical Engineering Journal, 2023)

Biochar accelerates soil organic carbon mineralization via rhizodeposit-activated Actinobacteria - Yingyi Fu; Yu Luo; Muhammad Auwal; Bhupinder Pal Singh; Lukas Van Zwieten; Jianming Xu (Biology and Fertility of Soils, 2022)

Metagenomic insights into soil microbial communities involved in carbon cycling along an elevation climosequences - Zhongmin Dai; Huadong Zang; Jie Chen; Yingyi Fu; Xuehua Wang; Huaiting Liu; Congcong Shen; Jianjun Wang; Yakov Kuzyakov; Joscha N. Becker; Andreas Hemp; Albert Barberán; et al. (Environmental Microbiology, 2021)
Summary Diversity and community composition of soil microorganisms along the elevation climosequences have been widely studied, while the microbial metabolic potential, particularly in regard to carbon (C) cycling, remains unclear. Here, a metagenomic analysis of C related genes along five elevations ranging from 767 to 4190 m at Mount Kilimanjaro was analysed to evaluate the microbial organic C transformation capacities in various ecosystems. The highest gene abundances for decomposition of moderate mineralizable compounds, i.e. carbohydrate esters, chitin and pectin were found at the mid‐elevations with hump‐shaped pattern, where the genes for decompositions of recalcitrant C (i.e. lignin) and easily mineralizable C (i.e. starch) showed the opposite trend (i.e. U‐shaped pattern), due to high soil pH and seasonality in both low and high elevations. Notably, the gene abundances for the decompositions of starch, carbohydrate esters, chitin and lignin had positive relationships with corresponding C compounds, indicating the consistent responses of microbial functional profiles and metabolites to elevation climosequences. Understanding of adaptation of microbial communities, potential function and metabolites to elevation climosequences and their influencing factors provided a new insight for the regulation of terrestrial C storage.

Rhizosphere microbiome modulated effects of biochar on ryegrass 15N uptake and rhizodeposited 13C allocation in soil - Yingyi Fu; Amit Kumar; Lijun Chen; Yuji Jiang; Ning Ling; Runze Wang; Qiong Pan; Bhupinder Pal Singh; Marc Redmile-Gordon; Lu Luan; Qin Li; Quan Shi; et al. (Plant and Soil, 2021)

Biochar decreased rhizodeposits stabilization via opposite effects on bacteria and fungi: diminished fungi-promoted aggregation and enhanced bacterial mineralization - Zhiyi Chen; Amit Kumar; Yingyi Fu; Bhupinder Pal Singh; Tida Ge; Hua Tu; Yu Luo; Jianming Xu (Biology and Fertility of Soils, 2021)